Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Pasien Pospartum Dengan HIV/AIDS Di Ruang Rindu B1 Obgyn RS. Haji Adam Malik Medan Tahun 2021 - Sianturi, Arisanti; Simamora, Lasria; Siagian, Chandra; Rangkuti, Natasya Pratiwy; Pramuditha, Loka Arfaah; Khairani, Maulidya (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2021)
HIV-AIDS is one of the endemic diseases that has been going on for a long time and has an effect on the patient’s psychology, namely anxiety and one of the contributing factors is family support. families with anxiety levels of postpartum patients with HIV-AIDS. This study uses a quantitative descriptive method with a cross sectional approach. The respondents in this study were 35 people who were carried out by the director of Adam Malik Medan. The instrument in this study used the Taylor Manifest Anxiety Scale (TMAS) questionnaire and to assess family support used a research instrument in the form of a questionnaire that had been prepared by the researcher. This study was analyzed using univariate and bivariate methods. chi square formula. The results of this study showed that most of the respondents (93.8%) showed a severe level of anxiety, most of the respondents (89.5%) stated that they received family support and from both stated that there was no significant relationship between the level of anxiety and family support (p value). = 0.536 ). The conclusion of this study is that there is no significant relationship between family support and the anxiety level of HIV-AIDS patients. This is due to patients who feel that any form of intervention in treatment cannot change their health status. This study provides input to the midwifery profession, hospitals , and other studies to pay more attention to the psychological problems experienced by HIV-AIDS patients.